Determination of total phenolic content in different varieties of date / Farhana Rosly - Rosly, Farhana (2009)
Date is well known among the Malaysian even though its origin is from the Middle Eastern countries. It is rich in simple sugars such as glucose and fructose (65 -80%), and a good source of fibers and some essential minerals, but low in fat and protein with no starch. The purpose of this study is to determine the total phenolic content present in different varieties of date by using Folin-Ciocalteu's method based on the Standard calibration curve of gallic acid measured at 650 nm using UV-Visible spectrophotometer (Perkin Elmer). The amount of total phenolic content obtained were, 1089.60+50.99 GAE/g initial weight for Mariami, 679.21+47.19 GAE/g initial weight for Rotab, 525.91+83.58 GAE/g initial weight for Qitarah, 328.55+74.63 GAE/g initial weight for Ajwa and 307.10+97.30 GAE/g initial weight for Tunisia. Mariami date was observed to have a higher total phenolic content compared to other dates analysed in this study. In conclusion, the highest total phenolic content was found in Mariami date and there were no significant relations between costs of each date with total phenolic content present there in.